The impact of customer value co-creation and relationship quality on relationship equity: Personality traits as a moderator - Omar N.A.; Kassim A.S.; Nazri M.A.; Sidek F. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by SCOPUS